2012
DOI: 10.3390/agriculture2040393
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea as an Agricultural Based Health Promoting Food: The Past Five to Ten Years

Abstract: Abstract:The consumption of tea originated in ancient China over 4000 years ago and is currently the second most popular beverage in the world after water. Tea is an aromatic beverage prepared by pouring hot water over cured leaves of the Camellia sinensis plant. The link between tea intake, most notably green tea, and health has resulted in intense research on the components responsible for preventing the onset of several chronic diseases, including atherosclerosis, cancer, obesity and diabetes. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Evidences of their role in the prevention of degenerative diseases such as cancer, cardiovascular diseases, and other degenerative diseases are emerging (Higdon and Frei ; Preedy ; Mirasoli and others ). Tea is an important source of polyphenols being found about 50% in weight of phenolic compounds (for green tea; Shi and Schlegel ). Several studies have shown that regular consumption of green tea ( camellia sinensis ) can reduce risks of cancers of colon (Sun and others ; Zhang and others ), breast (Ganmaa and others ; Kumar and others ), ovary (Nagle and others ), prostate, and lung (Cui and others ; Lambert ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences of their role in the prevention of degenerative diseases such as cancer, cardiovascular diseases, and other degenerative diseases are emerging (Higdon and Frei ; Preedy ; Mirasoli and others ). Tea is an important source of polyphenols being found about 50% in weight of phenolic compounds (for green tea; Shi and Schlegel ). Several studies have shown that regular consumption of green tea ( camellia sinensis ) can reduce risks of cancers of colon (Sun and others ; Zhang and others ), breast (Ganmaa and others ; Kumar and others ), ovary (Nagle and others ), prostate, and lung (Cui and others ; Lambert ).…”
Section: Introductionmentioning
confidence: 99%
“…For example the use of mechanical power and chemicals to increase agricultural output will be dangerous without regulation because the majority of farmers do not know the safe dosage to not damage the environment. Without regulation, farmers tend to overuse pesticides so that they will pollute the natural environment and the loss of beneficial flora and fauna, Shi and Vicki (2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research indicated that teas exhibit plenty pro-health properties including reducing obesity and blood glucose levels (Jigisha et al, 2012;Shi and Schlegel, 2012;Hosoda et al, 2003;He et al, 2009;Panagiotakos et al, 2009;Oba et al, 2010), concentration and immunity (Hammer, 2007), lowers total cholesterol levels (Sinija and Mishra, 2008), preventing several types of cancer (Huang et al, 2014;Michalak-Majewska, 2011;Seow et al, 2020;Sinija and Mishra, 2008;Jigisha et al, 2012;Shi and Schlegel, 2012), brain strokes (Arab et al, 2013), furthermore make possible more efficient heart muscle (Stańczyk, 2010;Jigisha et al, 2012;Shi and Schlegel, 2012), expansion of coronary and brain vessels and of bronchi, increasing body temperature (Stańczyk, 2010), diarrhea prevention (Doustfatemeh et al, 2016), contraction (Einöther and Martens, 2013), anti-inflammation (Sanliera et al, 2018;Sinija and Mishra, 2008;Shi and Schlegel, 2012), bactericidal and bacteriostatic effects, alleviation of burning and itching (Stańczyk, 2010;Jigisha et al, 2012), protects against solar radiation (Michalak-Majewska, 2011), antiviral and anticaries effects (Michalak-Majewska, 2011;Sanliera et al, 2018;Sinija and Mishra 2008;Jigisha et al, 2012), protection of the nervous system (Steptoe et al, 2007;Unno et al, 2017), slowing down the aging process (Stańczyk, 2010;…”
Section: Introductionmentioning
confidence: 99%